Do sex offender registration and notification requirements deter juvenile sex crimes? - Letourneau, Elizabeth J. (Criminal justice and behavior, 2010)
This study examined whether South Carolina?s sex offender registration and notification (SORN) policy was associated with a general deterrent effect on juvenile sex crimes. Using juvenile justice data from 1991 through 2004, trend analyses modeled the intervention effects of 1995 (the year South Carolina?s SORN policy was initially implemented) and 1999 (the year the policy was revised to include online registration). Initial results suggested a significant deterrent effect of SORN on first-time juvenile sex crimes. However, comparison analyses with nonsex offenses identified a similar effect on first-time robbery crimes. Follow-up analyses indicated that the apparent declines identified for first-time sex and robbery offenses were due to another legislative change, also enacted in 1995, that moved the prosecution of 16-year-old defendants from juvenile to adult court. When these cases were included in the database, follow-up analyses indicated no significant effect for the 1995 intervention year. Thus, South Carolina?s SORN policy was not associated with a general deterrent effect on juvenile sex crimes. Specific policy changes are suggested regarding the application of registration and notification requirements to juveniles.